2021
DOI: 10.1111/ans.16567
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of post‐operative pain in short versus long stitch technique for abdominal wall closure after elective laparotomy: a double‐blind randomized controlled trial

Abstract: Background Conventional mass closure uses suture‐to‐wound length ratio of 4:1 (‘long stitch’, LS). ‘Short stitch’ (SS) has a suture‐to‐wound length ratio of more than 4 and incorporates only the linea alba, which may reduce tension and pain. We compared the post‐operative pain after laparotomy closure using LS and SS. Methods Patients undergoing elective midline laparotomy through standardized incisions in two tertiary hospitals from February 2017 to September 2018 were randomized to either LS or SS. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We know of three randomized-controlled trials investigating the effect of the short stitch suture technique using polydioxanone [PDS] as the suture material [ 6 , 15 , 24 ]. Recently the ESTIOH-trial using p-4OHB (same thread as in this study) as alternative suture material involved 425 patients showed a clear benefit by cutting in half the incisional hernia incidence (3.3% vs 6.4%) compared to conventional 4:1 SL/WL ratio [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…We know of three randomized-controlled trials investigating the effect of the short stitch suture technique using polydioxanone [PDS] as the suture material [ 6 , 15 , 24 ]. Recently the ESTIOH-trial using p-4OHB (same thread as in this study) as alternative suture material involved 425 patients showed a clear benefit by cutting in half the incisional hernia incidence (3.3% vs 6.4%) compared to conventional 4:1 SL/WL ratio [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since most elective even larger oncological/ abdominal procedures are nowadays at least contemplated to be performed laparoscopically, our patient clientel here is regarded as an intermediate, probably even high risk group from a diagnostic standpoint (presenting disease), but also in general (underlying diseases). We know of three randomised-controlled trials investigating the effect of the `short stitch` suture technique using polydioxanone (PDS) as the suture material [6,15,19]. Recently the ESTIOH-trial using poly-4-OH butyrate (same thread as in this study) as alternative suture material involved 425 patients showed a clear benefit by almost cutting in half the incisional hernia incidence (3.3% vs 6.4%) compared to conventional 4:1 SL/WL ratio [16].…”
Section: Graphic Illustration (Figures 1-3)mentioning
confidence: 99%
“…According to the long stitch suture technique, the distance between the suture bite site and the wound incision should be 1 cm, and the inter-suture distance should also be 1 cm. This traditional approach of long stitch suturing includes the aponeurosis, sub-cuticular fat, and muscle within the suture [13]. If force is applied, the soft tissue gets compressed, leading to a greater amount of necrotic soft tissue and delayed wound healing [3,6,8,14].…”
Section: Introductionmentioning
confidence: 99%